The Cuban Revolution, Che and Lotta Continua - Gabbas, Marco (Tensões Mundiais, 2020)
The article analyses the influence of the Cuban Revolution and of Che on Lotta Continua (LC) – the main organisation of the Italian extra-parliamentary Left – from 1969 until 1974, through the pages of the newspaper Lotta continua. Che was a political and moral example for LC, which by 1974 went beyond myth and reached a balanced view on him. The issue of Che’s relevance in present-day Italy is also assessed.